2009
DOI: 10.1186/1471-2407-9-68
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer treatment and outcome in the elderly: an audit based on the Swedish rectal cancer registry 1995–2004

Abstract: BackgroundLimited information is available regarding the effect of age on choice of surgical and oncological treatment for rectal cancer. The objective of this study was to assess the influence of age on treatment and outcome of rectal cancer.MethodsWe utilized data in the Swedish Rectal Cancer Registry (SRCR) from patients treated for rectal cancer in Sweden in 1995–2004.ResultsA total of 15,104 patients with rectal cancer were identified, 42.4% of whom were 75 years or older. Patients ≥75 years were less lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 31 publications
9
34
2
Order By: Relevance
“…In contrast to our findings, several studies did observe less surgical treatment performed in older patients [7,8,[20][21][22][23][24]. Also, higher rates of non-surgical complications, mainly cardiopulmonary, in older patients have been reported [7,8,20,26].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, several studies did observe less surgical treatment performed in older patients [7,8,[20][21][22][23][24]. Also, higher rates of non-surgical complications, mainly cardiopulmonary, in older patients have been reported [7,8,20,26].…”
Section: Discussioncontrasting
confidence: 99%
“…Deviation from standard treatment in older patients with rectal cancer and comparable postoperative complication rates with younger patients are reported previously [7,[20][21][22][24][25][26]. In contrast to our findings, several studies did observe less surgical treatment performed in older patients [7,8,[20][21][22][23][24].…”
Section: Discussioncontrasting
confidence: 65%
“…14e16 Earlier studies have pointed out the absence of high quality evidence on how to treat elderly and comorbid patients. 17,18 However, despite the risk of an increased proportion of treatmentrelated complications in the elderly population or in patients with significant comorbidity, there are results indicating that also these patients gain from preoperative treatment. 9,12,19 In an earlier study we found that not only undertreatment is a problem in the selection process to preoperative treatment.…”
Section: Introductionmentioning
confidence: 94%
“…When analyzing the "Dutch TME" trial [17] and the Dutch cancer registries, Rutten et al [24] reported a low survival rate after radical surgery for patients >75 years and no benefit from the TME surgery. The death rate during the 6 months after surgery was close to 25% above the age of 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is difficult to define a standard approach for these elderly patients and to know what their outcome is. In a Swedish study, treatment of patients >70 years appeared suboptimal with less preoperative radiotherapy and more Hartman procedures with permanent stoma [17]. Only a few short reports deal with patients aged 70 years or above [19] or 80 years or above [11].…”
Section: Clinical Outcome Of Rectal Cancer In Patients ≥ 80 Years Trementioning
confidence: 99%